The limits of globalization : cases and arguments - Scott, Alan, 1956- (London ; New York : Routledge, 1997)
This book examines the concrete manifestations of the globalizing forces operating in the world today. It unpicks the rhetoric of globalization in political analysis, cultural theory and urban and economic sociology.
INTRODUCTION -- GLOBALIZATION: SOCIAL PROCESS OR POLITICAL RHETORIC? -- THE FUTURES OF BERLIN'S POTSDAMER PLATZ -- THE GLOBAL COMMON: THE GLOBAL, LOCAL AND PERSONAL -- DYNAMICS OF THE WOMEN'S PEACE MOVEMENT IN THE 1980s -- 'ACROSS THE UNIVERSE': THE LIMITS OF GLOBAL POPULAR CULTURE -- AN ASIAN ORIENTALISM? LIBAS AND THE TEXTURES OF POSTCOLONIALISM -- ELVIS IN ZANZIBAR -- CHINESE ENTREPRENEURSHIP: CULTURE AND ECONOMIC ACTORS -- GLOBALIZATION, URBAN CHANGE AND URBAN POLICIES IN BRITAIN AND FRANCE.
Includes bibliographical references (pages 327-349) and index.
English.
eBooks on EBSCOhost
Keywords: International economic relations -- Social aspects; International relations -- Social aspects; Cultural relations; Intercultural communication; Internationalism; International economic relations -- Case studies; Globalization; Relations économiques internationales -- Aspect social; Relations internationales -- Aspect social; Relations culturelles; Communication interculturelle; Internationalisme; Relations économiques internationales -- Cas, Études de; Mondialisation; internationalism; globalism; BUSINESS & ECONOMICS -- International -- General; BUSINESS & ECONOMICS -- International -- Economics; Cultural relations; Globalization; Intercultural communication; International economic relations; International economic relations -- Social aspects; International relations -- Social aspects; Internationalism; Electronic books; Case studies